Analysis of Financial and Non-Financial Performance of Public Sector Organizations - Muchran, Muchriana; Idrawahyuni, Retno Pinasti Putri (Contemporary Journal on Business and Accounting, 2024)
Purpose – This study aims to measure the implementation of the work program of Makassar Hajj Hospital, both from financial and non-financial aspects in 2019-2021 Design/methodology/approach – Using a Balanced Scorecard approach to analyze performance, focusing on financial aspects such as economics, efficiency, and effectiveness, as well as non-financial aspects such as customer satisfaction, internal business processes, and growth and learning Findings – Balanced Scorecard that has 4 perspectives Originality – This thesis introduces financial and non-financial aspects of the Balanced Scorecard approach Keywords: Financial Performance, Non-financial Performance, Balanced Scorecard Paper Type Research Result